Kid Influencers as content creators: Legal implications - Fernández Blanco, Elena; Ramos Gutiérrez, Mercedes (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Children belonging to Generation Alpha have grown up in a totally digital environment. They use and know from a young age mobile devices, virtual assistants, toys with Artificial Intelligence, which makes them hyper-connected and become true technological experts. In this context, it is not unusual to find them actively participating in different platforms and social networks as content creators. True influencers where brands and advertising have seen an opportunity to reach minors. The content created by this generation is mostly advertising and does not comply with the regulations in charge of protecting minors in this sector.